The influence of age and sex on speed–strength performance in children between 10 and 14 years of age - Warneke, Konstantin; Wagner, Carl Maximilian; Konrad, Andreas; Kadlubowski, Björn; Sander, Andre; Wirth, Klaus; Keiner, Michael (Frontiers in Physiology, 2023)
Speed-strength performance is important during human movements such as jumping, sprinting, and change of direction (COD) tasks, which are a substantial part of sports practice. Sex and age seem to influence performance output in young persons; however, only a few studies have focused on the influence of sex and age measured via standard protocols of performance diagnostics. Therefore, the aim of this study was to investigate the influence of age and sex on linear sprint (LS), COD sprint, countermovement jump (CMJ) height, squat jump (SJ) height, and drop jump (DJ) height performance in untrained children and adolescents via a cross-sectional analysis. This study included 141 untrained male and female participants of 10–14 years of age. The results showed an influence of age in male participants on speed-strength performance, while in female participants, age did not influence performance parameters significantly. Moderate to high correlations between sprint and jump performance (r = 0.69–0.72), sprint and COD sprint performance (r = 0.58–0.72), as well as jump and COD sprint performance (r = 0.56–0.58) were found. Based on the data of this study, it appears that the growth phase from 10 to 14 years of age does not necessarily lead to improvements in athletic performance. To ensure holistic motor development, female subjects, in particular, should be provided with specific training interventions with a focus on strength and power.